Correlation Of Change Communication Factorswith Perceived Success Of Change Initiatives In A Selected Organization - Abdullah, Mohammad Firdaus Low (2009)
Everybody is aware of the fact that today, everything (almost everything) is changing and the only constant is change itself. Regardless of who we are – students, workers, stakeholders, shareholders and so forth, we are all subjected to various types of changes in our lives. In other words, change is a part of our life. Change has intrigued, scared, excited, and mystified man for many centuries and continues to challenge individuals from all walks of life, yet it is inevitable and has become the very nucleus of human life (Szamosi & Duxbury, 2002). Correspondingly, the term